Post-exposure prophylaxis for non-occupational exposure to HIV: current clinical practice and opinions in the UK. Issue 2 (1st April 2002) - Giele, C M; Maw, R; Carne, C A; Evans, B G
Abstract : Objectives: To assess the frequency and nature of requests for post-exposure prophylaxis following non-occupational exposure (NONOPEP) to HIV and to describe variations in practice and opinions on the need for its administration at UK genitourinary medicine (GUM) clinics. Method: A retrospective survey was carried out of physicians representative of all UK GUM clinics using self completed questionnaires requesting information for January to December 1999. The number of requests for NONOPEP, reasons for the requests, the number prescribed, and physician opinions regarding the justification for its administration were noted. Results: The number of requests and prescriptions for NONOPEP increased fourfold and sevenfold respectively in comparison with a survey from 1997. Of 242 requests, 130 people were prescribed NONOPEP. Half the requests followed sexual exposures between known HIV discordant couples. Requests for NONOPEP were received by 56 of 132 (42%) clinics, with nine clinics receiving over half of them (145/242, 60%). Similarly, over half the prescriptions for NONOPEP (83/130, 64%) were given by six of 39 prescribing clinics. Most physicians thought that post-exposure prophylaxis (PEP) was justified for people exposed to a known HIV positive source patient resulting from sexual assault or unprotected receptive anal or peno-vaginal sex. Conclusion: The use of NONOPEP has increased since the last survey and there is considerable variation between GUM clinics in practice and beliefs regarding administration of NONOPEP.